THE RELATIONSHIP OF ENVIRONMENTAL CONDITIONS WITH FISHERMAN'S HAPPINESS ONLIMBUNGANVILLAGESUBDISTRICT RUMBAI PESISIR PEKANBARU CITY OF RIAU PROVINCE - Mustikawati '; Kusai '; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research on the Relationship of Environmental Condition With Fisherman's Happiness was held in January 2017 in Limbungan Village, Rumbai Pesisir Sub District, Pekanbaru City, Riau Province. This study aims to determine what factors determine the happiness of fishermen and know the relation of environmental conditions with the happiness of fishermen. The method used in this research is the survey method that is used Spearman Rank and the number of respondents in this study are 30 respondents who processed using SPSS 20 applications.From the results of the research analysis, it was found that the happiness of fishermen in Limbungan Village was influenced by age factor, successful year, number of dependents, income, work experience, housing condition, social relationship, religious activity and security. From several factors, the relationship of environmental conditions with the happiness of fishermen in Limbungan village significant correlated with social relations with the value of rs = 0,393 * and religious activity with value rs = 0,424 *. Values on social relations and religious activities are categorized having a significant relationship will fishman’s happinees.Keywords: relation, environmental condition, fisherman's happiness